Development of a patient centred, structured, individually tailored, multi-component intervention to promote rehabilitation and recovery after critical illness: content, theory, and construction. [version 2; peer review: 1 approved, 2 approved with reservations] - Julie Bruce; Ella Terblanche; Sallyanne Duncan; Brenda O'Neill; Bronwen Connolly; Danny McAuley; Rachel Clarke; Jill Costley; Penelope Firshman; Judy Martina Bradley (NIHR Open Research, 2025)
Background/aims This paper describes the development (content, theory, and construction) of a patient-centered, structured, individually tailored, multicomponent intervention (the iRehab intervention) to promote rehabilitation and recovery after critical illness. Methods The intervention was informed by the MRC framework for complex interventions and underpinned by existing literature and psychological theories. Key stakeholders included patients who had been in intensive care and multidisciplinary staff with experience in providing healthcare and undertaking research. Results The final intervention includes four core components: 1. weekly discussion and guidance regarding symptom management; 2. targeted exercise and physical activity; 3. support for psychological well-being; 4. peer support and information provision. These are packaged as a program to support rehabilitation and recovery after ICU discharge. Programme duration: Six weeks. Format: Weekly one-to-one remote needs assessment to identify individual participant symptoms and provide management plans, exercises, and strategies to best support recovery. Participants are encouraged to attend weekly group-based remote exercise sessions and group-based remote support sessions (iRehab Café). Mode of delivery: Remote delivery facilitated by online platforms such as Microsoft Teams or Zoom supported with video platform BEAM©, and delivery can also be supported by telephone. The preferred mode of remote delivery is agreed with the participant, and potential barriers to implementation are considered. Manuals are posted to all participants to support intervention delivery. Discussion/conclusion This paper reports the content, theory and construction of the iRehab intervention. The iRehab intervention is currently being tested in a multicenter RCT (iRehab ISRCTN11266403), and the details reported in this paper will help with understanding of the intervention, interpretation of the findings, and replication of the intervention. Detailed intervention manuals will be available upon the completion of the trial.